Nilai dan Pendidikan Nilai di Sekolah - Maimun, Agus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
Value is the essence which causes it to be appropriate to be done by human beings. Value has close relationship with goodness. Although both of them are not same. remembering that a good thing does not always have high value for someone or on the contrary, in order value to be a part of individual, then it needs to be given through educational process. Educational value is not only one thing that increases. On the other hand, it is an essential thing in the whole educational process. Some religious values and humanity values that need to be fought in educational process in school are ikhlas, tawaddu ', ashamed, qonaah, zuhud, iffah, eagerness, honest, care ness and empathy, cooperative, brave, great heart and commitment, fear, like helping, honesty and integrity, humor, independence and self confidence, self discipline, loyalty, patient, feel proud, cleaver, respect, responsible and tolerance. However, approach that is used in educational value includes evocation approach, inculcation approach, awareness approach, moral reasoning, value analyses approach, value clarification, commitment approach, and union approach.